Dynamics of Leadership, Power, and Negotiation in Managerial Decisionmaking - Teuku Fajar Shadiq; Hani Hasanah; Zainuddin (Journal Research of Social Science, Economics, and Management, 2025)
Sustainable and adequate urban sanitation development is a fundamental aspect of realizing healthy, inclusive, and resilient cities. However, local fiscal limitations, suboptimal institutional capacity, and the low involvement of multiple stakeholders pose significant challenges in providing safe sanitation services in Depok City and Bogor City. The Public-Private Partnership (PPP) scheme is viewed as a strategic alternative to bridging financing gaps while improving the efficiency and quality of urban sanitation services. This study aims to analyze the challenges of urban sanitation development in Depok and Bogor, identify key factors influencing private sector involvement through PPP schemes, and formulate sustainable urban sanitation development strategies involving the private sector. The study employs a descriptive qualitative approach with data collection techniques including in-depth interviews, observations, and document studies with key informants from local governments, business actors, sanitation practitioners, and community representatives. The results indicate that the main challenges include weak tariff regulation, limited inter-agency coordination, low public awareness, and inadequate integrated fecal sludge management services. The key factors influencing private sector engagement include legal certainty, project economic scale, availability of technical data, and the readiness of local government institutions. This research recommends strengthening regulations and planning, establishing Badan Layanan Umum Daerah (BLUD) for sanitation management, enhancing multi-stakeholder collaboration, and developing attractive PPP schemes for private partners as part of efforts to accelerate the achievement of safe and sustainable urban sanitation targets.